Interventions to improve media coverage of medical research: a codesigned feasibility and acceptability study with Australian journalists - Brooke Nickel; Ray Moynihan; Alexandra Barratt; Kirsten J McCaffery; Loai Albarqouni; Tessa Copp; Thomas Dakin; Liam Mannix (BMJ Open)
Objectives Although the media can influence public perceptions and utilisation of healthcare, journalists generally receive no routine training in interpreting and reporting on medical research. Given growing evidence about the problems of medical overuse, the need for quality media reporting has become a greater priority. This study aimed to codesign and assess the feasibility of a multicomponent training intervention for journalists in Australia.Design A small pragmatic feasibility study using a pre- and postdesign.Setting 90 min online workshop.Participants Eight journalists currently working in Australia, recruited through the study’s journalist advisor and existing contacts of the researchers.Intervention The training intervention covered a range of topics, including study designs, conflicts of interest, misleading medical statistics, population screening and overdiagnosis. The intervention also provided tools to help journalists with reporting, including a Tip Sheet and list of expert contacts in health and medicine. Preworkshop and postworkshop questionnaires were administered via Qualtrics.Measures Acceptability and feasibility of the intervention, and journalists’ knowledge of overdiagnosis and common issues with health stories. Quantitative results were analysed descriptively using SPSS. Qualitative data were thematically analysed.Results All participants completed preworkshop and postworkshop questionnaires, and 6 completed the 6-week follow-up (75% retention). Feasibility findings suggest the intervention is acceptable and relevant to journalists, with participants indicating the workshop increased confidence with reporting on medical research. We observed increases in knowledge preworkshop to postworkshop for all knowledge measures on overdiagnosis and common issues with media coverage of medicine. Analysis of free-text responses identified several areas for improvement, such as including more examples to aid understanding of the counterintuitive topic of overdiagnosis and more time for discussion.Conclusions Piloting suggested the multicomponent training intervention is acceptable to journalists and provided important feedback and insights to inform a future trial of the intervention’s impact on media coverage of medicine.